PENGGUNAAN METODE BEST-WORST SCALING UNTUK MENGANALISIS HAMBATAN DALAM PEMBELIAN PRODUK SECARA ONLINE PADA KONSUMEN MUSLIM - Cut Mega Putri; Alfian Anas; Muzakir Muzakir (Procuratio : Jurnal Ilmiah Manajemen, 2023)
This study examined Muslim consumer perceptions of the relative importance of selected barriers of using online shopping in Aceh Province, Indonesia. A survey was conducted on a total of 560 undergraduate students in Meulaboh and Banda Aceh. Ten obstacles in conducting online shopping attributes were evaluated. A best-worst object scaling with a balanced incomplete block design was adopted to investigate their preference towards obstacles in conducting online shopping. Each respondent answered 30 questions, which asked respondents to select the most and the least important attributes in a choice scenario. Each question includes a random combination of three attributes. The relative importance of each attribute was evaluated using counting analysis. Overall, the most important barriers to conducting online shopping were “identity theft”, “high shipping cost”, “product arrived late”, “damaged products”, and “products shipped differently”. Whereas “dishonest seller”, “counterfeit products”, “unwarranted products”, “conflict with the seller” and “slow internet connection” are the least important attribute. This study suggests the most important barriers to online shopping for Muslim consumers’ perceptions in Indonesia. The importance rankings provide rich information for implementing online shopping in Indonesia. Thus, the findings might deserve consideration in online shopping policy design. However, the heterogeneities in preference might need further exploration. Penelitian ini dilakukan untuk mengetahui persepsi konsumen Muslim tentang kepentingan relatif dari hambatan yang dipilih dalam menggunakan belanja online di Provinsi Aceh, Indonesia. Survei dilakukan terhadap total 560 mahasiswa S1 di Meulaboh dan Banda Aceh. Sepuluh atribut hambatan dalam melakukan belanja online dievaluasi. Penskalaan objek terbaik-terburuk dengan desain blok tidak lengkap yang seimbang diadopsi untuk menyelidiki preferensi mereka terhadap hambatan dalam melakukan belanja online. Setiap responden menjawab 30 pertanyaan, yang meminta responden untuk memilih atribut yang paling penting dan paling tidak penting dalam skenario pilihan. Setiap pertanyaan menyertakan kombinasi acak dari tiga atribut. Kepentingan relatif dari setiap atribut dievaluasi menggunakan analisis penghitungan. Secara keseluruhan, hambatan terpenting untuk melakukan belanja online adalah “pencurian identitas”, “ongkos kirim tinggi”, “produk lama tiba”, “produk rusak”, dan “produk dikirim berbeda”, Sedangkan “penjual tidak jujur”, “produk palsu”, “produk tidak bergaransi”, “konflik dengan penjual” dan “koneksi internet lambat”. adalah atribut yang paling tidak penting. Studi ini menunjukkan hambatan paling penting dalam belanja online untuk persepsi konsumen Muslim di Indonesia. Peringkat kepentingan memberikan informasi yang kaya untuk menerapkan belanja online di Indonesia. Dengan demikian, temuan tersebut mungkin layak dipertimbangkan dalam desain kebijakan belanja online. Namun, heterogenitas dalam preferensi mungkin perlu eksplorasi lebih lanjut.